Методы математической физики. Специальные функции. Уравнения математической физики учебное пособие для вузов - Багров физик профессор Томского государственного университета; Белов; Задорожный математик доцент Томского политехнического университета, кандидат физико-математических наук; Трифонов российский физик, математик профессор Томского политехнического университета, доктор физико-математических наук (Изд-во ТПУ, 2012)
This textbook presents the theory of special functions and the methods for solving integral equations and first order and second order partial differential equations. The theoretical material is consistent to the existing courses of higher mathematics for engineering and physical specialties of universities. The textbook can be useful to the graduate students, magisters, and postgraduates specializing in theoretical and mathematical physics. The textbook is intended for students and post-graduates of physical and engineering departments.